Can slow-moving ions explain hysteresis in the current–voltage curves of perovskite solar cells?. Issue 4 (26th February 2016) - Richardson, Giles; O'Kane, Simon E. J.; Niemann, Ralf G.; Peltola, Timo A.; Foster, Jamie M.; Cameron, Petra J.; Walker, Alison B.
Abstract : We have developed a charge transport model that explicitly accounts for ion migration. This model has been used to interpret measured current–voltage characteristics that show hysteresis. Abstract : The hypothesis that ion motion is responsible for anomalous hysteresis in the current–voltage curves of perovskite solar cells is investigated through a combination of electrical transport modelling and experimental measurements. In a combined computational and experimental study, good agreement is obtained between experiment and the results of a charge transport model covering mixed ionic-electronic conduction. Our model couples electrons, holes and defect mediated ion motion suggesting that slow moving ions are indeed the origin of the hysteresis. The magnitude of the ion diffusion coefficient required to match experiment and theory, ∼10 −12 cm 2 s −1, depends on the cell, but is similar to that predicted by microscopic theory of vacancy mediated diffusion. The investigation is extended to preconditioning procedures which are known to substantially influence the hysteresis. The method developed for solving the stiff equations in the drift diffusion model is widely applicable to other double layer problems occurring in electrochemical applications such as the evolution of transmembrane potentials in living cells.